2022
DOI: 10.3390/biology11020155
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species, Antioxidant Responses and Implications from a Microbial Modulation Perspective

Abstract: Plants are exposed to various environmental stresses in their lifespan that threaten their survival. Reactive oxygen species (ROS), the byproducts of aerobic metabolism, are essential signalling molecules in regulating multiple plant developmental processes as well as in reinforcing plant tolerance to biotic and abiotic stimuli. However, intensified environmental challenges such as salinity, drought, UV irradiation, and heavy metals usually interfere with natural ROS metabolism and homeostasis, thus aggravatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(83 citation statements)
references
References 343 publications
(392 reference statements)
1
82
0
Order By: Relevance
“…Methods of chlorophyll fluorescence revealed a hazard and suggested that manufacturing operations were not balanced [82,83]. Drought stress causes plants to be adapted accordingly by regulating their stomata movement, adjusting their osmotic balance, and mounting an antioxidatant defense [8,84]. However, a protracted period of high-intensity limited water conditions might slow plant development, alter the morphological structure and biomass distribution pattern in tomato crops (Solanum lycopersicum L.), or cause mortality [15,85].…”
Section: Effect Of Drought Stress Conditions On Photosynthesis and St...mentioning
confidence: 99%
See 3 more Smart Citations
“…Methods of chlorophyll fluorescence revealed a hazard and suggested that manufacturing operations were not balanced [82,83]. Drought stress causes plants to be adapted accordingly by regulating their stomata movement, adjusting their osmotic balance, and mounting an antioxidatant defense [8,84]. However, a protracted period of high-intensity limited water conditions might slow plant development, alter the morphological structure and biomass distribution pattern in tomato crops (Solanum lycopersicum L.), or cause mortality [15,85].…”
Section: Effect Of Drought Stress Conditions On Photosynthesis and St...mentioning
confidence: 99%
“…Carotenes are classified into two types: hydro-carbon carotenes [83], which include lycopene and xanthophylls, and carotene, which differs from the former due to the inclusion of lutein. The enzymatic antioxidant system contains carotenes, tocopherol, ascorbate, and enzymes such as APX, POD, SOD, polyphenol oxidase, glutathione reductase (GR), and CAT was, protecting carotenoids from the damaging of ROS [8,88,[94][95][96][97]. The enzymatic antioxidant system, which contains carotenoids, also protects carotenoids from ROS.…”
Section: Carotenoidsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tocopherols capacity to scavenge or quench lipid peroxides, oxygen radicals, or singlet oxygen, resulting in ROS detoxification, is the most significant role of tocopherols in alleviating abiotic stress-induced damage. Mutant and transgenic techniques that result in the loss or increase of function of tocopherol pathway genes likely to shed light on the compound’s role in plants ( Waqas et al, 2019 ; Zandi and Schnug, 2022 ). ROS are produced in response to various abiotic stimuli including dryness, salt, low temperature, and heavy metals, which harm membrane-containing organelles.…”
Section: Proficiency Of Biochemical Associated With Stress Tolerancementioning
confidence: 99%